A should costing approach for manufacturing companies. (18th January 2020) - Mandolini, Marco; Favi, Claudio; Peruzzini, Margherita; Germani, Michele
One of the most important drivers for developing competitive products is cost. However, scientific and industrial communities are missing an effective cost management framework (including a solid method and a reliable tool) for supporting the product development process, from the initial design phases to procurement. For this reason, the paper presents a holistic 'should costing' methodology able to foster collaboration on cost-oriented solutions among company's departments. The 'should costing' methodology and the related tool enable a systematic review of cost evolution, focusing on the opportunities to reduce costs, from the conceptual design stage through the overall production stages. In addition, the paper presents requirements for efficient implementation of a should-cost tool considering enterprise software solutions already available in manufacturing companies. A couple of companies (product manufacturers) adopted the recommended 'should costing' framework and quantitative and qualitative evaluations of the deployment process are presented as results. The benefits related with the adoption of the proposed should costing approach in relation with the traditional product development process is presented as well.